TANGGUNG JAWAB HUKUM PEMEGANG SAHAM YANG MENOLAK MENYETORKAN MODAL SAAT PERSEROAN MENINGKATKAN MODAL - Gemalya Adji Pangestu Dama; Maryano Maryano; Hedwig Adianto Mau (CORPUS JURIS : JURNAL ILMU HUKUM, 2026)
This research examines the legal liability of shareholders who refuse to contribute capital when a company increases its capital, potentially disrupting the company's financial stability and harming creditors and third parties. Using normative juridical research with statutory and conceptual approaches, this study analyzes the legal construction of capital contribution obligations and the forms of legal accountability. The findings indicate that the obligation to contribute capital is essentially a right that shareholders may exercise, yet under certain circumstances it may give rise to legal liability when performed in bad faith and causing harm to the company. Refusal to contribute capital not only results in share dilution but may also trigger legal accountability, including exceptions to limited liability through the piercing the corporate veil doctrine. Therefore, it is necessary to strengthen regulations in the articles of association and shareholders' agreements to prevent disputes and ensure legal certainty.